Nitrogen doped graphitic carbon ribbons from cellulose as non noble metal catalyst for oxygen reduction reaction. (24th August 2016) - Wu, Xiaoxian; Yu, Xiang; Lin, Zhipeng; Huang, Jilin; Cao, Linmin; Zhang, Bodong; Zhan, Yunfeng; Meng, Hui; Zhu, Yi; Zhang, Yuanming
Abstract: Nitrogen doped graphitic carbon ribbons are prepared by simultaneously graphitization and nitrogen doping of nano crystalline cellulose at high temperature. Ferrous salt works as catalyst for graphitization, without which amorphous carbon is resulted. The graphitic carbon ribbons and amorphous carbon are compared in detail in morphology, crystalline structure, defects, nitrogen groups and ORR activity by means of SEM, TEM, Raman, XRD, XPS and electrochemical characterizations. It is found the nitrogen doped graphitic carbon ribbons has comparable ORR activity with Pt/C catalyst in alkaline medium, which is much better than nitrogen doped amorphous carbon. The improved ORR activity is ascribed to the nitrogen group introduced by NH3 treatment of graphitic carbon. The as prepared material can work as efficient non noble metal catalyst for the oxygen reduction reaction. Highlights: Cellulose-based non noble metal catalyst for oxygen reduction reaction is studied. The cellulose-derived carbon is doped with NH3 . Comparable ORR activity with Pt/C catalyst is reached.